Effect of 1-methylcyclopropene and retain® on quality attributes of 'Kristali' pears after short or long term cold storage - Pantelidis, Georgios E.; Vasilakakis, Miltiadis; Manganaris, George A. (My University, 2010)
The effect of prestorage treatment of ‘Kristali’ pears with two forms of 1-methylcyclopropene (1-MCP) and ReTain® on storage performance after various durations of cold storage with subsequent exposures at 20°C was studied. Treatments included immersion in water solutions of 1 mg/L 1-MCP concentration and of 1.28 mmol L-1 ReTain®, while gas treated fruits were enclosed in airtight plastic chambers for 20 h at 18°C with a 1-MCP concentration of 1 μl/L. Treated and non-treated (control) fruits were stored at 0°C for 0, 2, 4 or 6 months and then held for 4 days at 20°C. Control fruits, after 6 months cold storage and one day maintenance at 20°C, collapsed rapidly. Application of 1-MCP in enclosed area resulted in decreased ethylene and CO2 production (98 and 45%, respectively) during the four months of cold storage compared to the control. Both forms of 1-MCP delayed fruit softening to a greater extent than ReTain® did. L* values were higher in both forms of 1-MCP-treated fruits after 4 or 6 months of cold storage. Hue angle values were higher only in fruits treated with 1-MCP in enclosed areas after 2, 4 or 6 months of cold storage. Soluble solids content of all treated fruits were higher by 6-8% compared to control fruit after 4 or 6 months of cold storage. Chlorophyll content of the peel of fruits after 6 months cold storage was 30% higher in ReTain®-treated fruits. Total phenol content and antioxidant activity of all fruits decreased during cold storage, however, all values were higher in treated than in non treated fruits. Overall, our data indicated that when 1-MCP was provided in enclosed areas was the most effective and both forms of 1-MCP gave better quality fruits compared to ReTain®
Keywords: Pear; Cold storage; Antioxidants; Chlorophyll; Ethylene; Phenols; Fruits